RESEARCH ON MODULE PARTITION FOR REMANUFACTURING PARTS TO BE ASSEMBLED - Yin, Lu; Yang, Fangyan; Zhu, Fuping; Qin, Qin (The South African Journal of Industrial Engineering, 2022)
To solve the technical, economic and environmental problems in the remanufacturing process of decommissioned machine tools, this study proposes a module partition method for remanufacturing retired machine tools. Through an analysis of the economic, accuracy, environment-friendly, and functional and physical interactivity principles, this study applies the fuzzy cluster method (FCM) to analyse the modularity of the components to be assembled. It establishes the correlation matrix between the parts, from which a module division scheme is obtained. Finally, a case study is presented to verify the feasibility of the module division method.